Challenges of Multimorbidities in the Era of an Aging Population. Issue 2 (April 2016) - Jung, Minsoo
Abstract : The health care system introduced a reimbursement system based on the existing care when the prevalence rate of acute diseases was still. However, the types of diseases in developed countries are mostly noncommunicable diseases such as cancer or vascular disease, and thus, it impossible to fully recover from these chronic diseases. The increase in noncommunicable diseases is related to unhealthy lifestyle habits such as smoking, heavy drinking, and lack of exercise. Thus, the health care system is changing by improving the prevention of diseases and promoting healthy lifestyles. However, multimorbidities have emerged as an important concept in this process. In countries where the population is rapidly aging, those who have multimorbidities have become a burden to the health care system's revenue, manpower, and service quality. Therefore, health care reform to cope with those who are aging and have multimorbidities is necessary to establish. Reform measures can consist of the following suggestions. First, proper medical guidelines for multiple diseases need to be developed. Second, professional manpower should be trained. Third, the reimbursement system should be improved to relieve those with multimorbidities. Fourth, disease prevention services should be improved. Finally, instruments to measure health care service quality for chronic disease need to be developed.